Breast cancer signatures for invasiveness and prognosis defined by deep sequencing of microRNA - Volinia, Stefano (National Academy of Sciences, 2012)
The transition from ductal carcinoma in situ to invasive ductal carcinoma is a key event in breast cancer progression that is still not well understood. To discover the microRNAs regulating this critical transition, we used 80 biopsies from invasive ductal carcinoma, 8 from ductal carcinoma in situ, and 6 from normal breast. We selected them from a recently published deep-sequencing dataset [Farazi TA, et al. (2011) Cancer Res 71:4443–4453]. The microRNA profile established for the normal breast to ductal carcinoma in situ transition was largely maintained in the in situ to invasive ductal carcinoma transition. Nevertheless, a nine-microRNA signature was identified that differentiated invasive from in situ carcinoma. Specifically, let-7d, miR-210, and -221 were down-regulated in the in situ and up-regulated in the invasive transition, thus featuring an expression reversal along the cancer progression path. Additionally, we identified microRNAs for overall survival and time to metastasis. Five noncoding genes were associated with both prognostic signatures—miR-210, -21, -106b*, -197, and let-7i, with miR-210 the only one also involved in the invasive transition. To pinpoint critical cellular functions affected in the invasive transition, we identified the protein coding genes with inversely related profiles to miR-210: BRCA1, FANCD, FANCF, PARP1, E-cadherin, and Rb1 were all activated in the in situ and down-regulated in the invasive carcinoma. Additionally, we detected differential splicing isoforms with special features, including a truncated EGFR lacking the kinase domain and overexpressed only in ductal carcinoma in situ.